2017
DOI: 10.1111/iji.12306
|View full text |Cite
|
Sign up to set email alerts
|

IL33 and IL1RL1 variants are associated with asthma and atopy in a Brazilian population

Abstract: Atopic asthma is a chronic inflammatory disease in airways resulting from genetic and environmental factors, characterized by production of the Th2 cytokines interleukin-4 (IL-4), interleukin-5 (IL-5) and interleukin-13 (IL-13). Interleukin-33 (IL-33) appears to be a potent inducer of Th2 immune response. This occurs when IL-33 binds and activates its receptor, the membrane ST2 (ST2L) in mast cells, dendritic cells, basophils, eosinophils, innate lymphoids and Th2 cells, leading to the release of these cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 61 publications
3
19
0
1
Order By: Relevance
“…A strong linkage of the loci for IL‐1R4, as well as its ligand IL‐33, has been reported especially for allergic asthma (reviewed in ), and recent studies underscore this finding in different populations. Loss‐of‐function mutations in IL‐33 in allergic patients as well as in IL‐1R4 were identified, supporting the findings in genome‐wide association studies that identified the IL‐33/IL‐1R4 pathway as the most relevant factor in allergy . Besides allergic asthma, increased levels of IL‐33 have been found in many disorders associated with acute or chronic inflammation (reviewed in ) such as in the intestine (reviewed in ) and arthritis.…”
Section: Focus On the Il‐1r Familysupporting
confidence: 80%
See 1 more Smart Citation
“…A strong linkage of the loci for IL‐1R4, as well as its ligand IL‐33, has been reported especially for allergic asthma (reviewed in ), and recent studies underscore this finding in different populations. Loss‐of‐function mutations in IL‐33 in allergic patients as well as in IL‐1R4 were identified, supporting the findings in genome‐wide association studies that identified the IL‐33/IL‐1R4 pathway as the most relevant factor in allergy . Besides allergic asthma, increased levels of IL‐33 have been found in many disorders associated with acute or chronic inflammation (reviewed in ) such as in the intestine (reviewed in ) and arthritis.…”
Section: Focus On the Il‐1r Familysupporting
confidence: 80%
“…Loss-of-function mutations in IL-33 in allergic patients 193 as well as in IL-1R4 [194][195][196] were identified, supporting the findings in genome-wide association studies that identified the IL-33/IL-1R4 pathway as the most relevant factor in allergy. 190 Besides allergic asthma, increased levels of IL-33 have been found in many disorders associated with acute or chronic inflammation (reviewed in 197) such as in the intestine (reviewed in 198) and arthritis.…”
Section: Role In Diseasessupporting
confidence: 79%
“…The analyses were performed under an additive model and the Odds Ratio (OR) was estimated, as well as 1000 permutations procedures was used to estimate the statistical significance of multiple correlation tests in the genetic association analysis [29,30]. Results obtained from this analysis having a confidence interval of 99.0% and a P-value less than 0.01 were considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐33 is also implicated in allergy and asthma . For example, single nucleotide polymorphisms (SNPs) in the IL‐33 gene were associated with the development of allergic rhinitis and asthma . IL‐33/ST2 signaling may also promote local progression and metastasizing of myeloproliferative neoplasms, gastric cancer, colon cancer, and breast cancer …”
Section: Introductionmentioning
confidence: 99%